Dramatization as a teaching strategy for learning customer service in students of the technical career of Executive Secretary of Colegio Técnico Profesional de Turrialba in the year 2024 - Loaiza Araya , Álvaro (2024)
The article is about the use of dramatization as a didactic strategy for teaching customer service to students in the Executive Secretariat technical career. Its objective is to explore how this strategy can contribute to learning and to understand students' perception of it. A qualitative and exploratory research approach was employed. Findings revealed significant benefits of the didactic strategy, and the main conclusion was that it facilitated students to put into practice actions related to learning customer service and to enjoy the learning process.